2007
DOI: 10.2304/ciec.2007.8.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Vouchers in Hong Kong: A New Milestone of Early Childhood Education?

Abstract: The Hong Kong government has recently introduced a voucher system to early childhood education, indicating that the new policy is a milestone in the field. The overall goal of the policy is to improve the provision of early childhood education for the benefit of the children. Public debates reveal the unfamiliar nature of the subject to the local community and as a result, it has left many issues and assumptions unexamined and unchallenged. In effect, the new policy is an obvious neoliberal response to complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In the case of the US it has been documented that, despite a comprehensive voucher system, accessibility for families in poverty is not evident (Weinraub et al ., ) and in the case of the Netherlands is has also been demonstrated that accessibility in poor urban areas and in rural areas has significantly decreased since the marketization. The problematic functioning of vouchers for poor families in market‐oriented systems has also been documented in California (Whitebook, Kipnis and Bellm, ), Canada (Cleveland, ), Hong Kong (Yuen, ) and Taiwan (Lee, ).…”
Section: Conclusion: a Plea For Circumstances‐oriented Equality Of Opmentioning
confidence: 97%
“…In the case of the US it has been documented that, despite a comprehensive voucher system, accessibility for families in poverty is not evident (Weinraub et al ., ) and in the case of the Netherlands is has also been demonstrated that accessibility in poor urban areas and in rural areas has significantly decreased since the marketization. The problematic functioning of vouchers for poor families in market‐oriented systems has also been documented in California (Whitebook, Kipnis and Bellm, ), Canada (Cleveland, ), Hong Kong (Yuen, ) and Taiwan (Lee, ).…”
Section: Conclusion: a Plea For Circumstances‐oriented Equality Of Opmentioning
confidence: 97%
“…As Cleveland and Krashinksy (2004) noted, those who favor demand-side funding typically believe that childcare markets work relatively well and that it is important to preserve parental choice. However, studies in countries or regions so diverse as California (Whitebook, Kipnis, & Bellm, 2007), Canada (Cleveland et al, 2007), Taiwan (Lee, 2006), Hong Kong (Yuen, 2007), or The Netherlands (Noailly et al, 2007), showed that demand-side funding tends to increase inequalities in enrolment, despite the rhetoric of choice and despite the use of vouchers for poor families. As an example, the Dutch Planbureau (planning bureau) calculated that the marketization of childcare, introduced in The Netherlands in 2005, led to a decrease of providers in rural areas and poor neighborhoods of urban areas, and to an increase of providers in more affluent urban areas, leading to inequalities in actual choice (Noailly et al, 2007).…”
Section: Accessibility Mattersmentioning
confidence: 99%
“…Although Friedman's conception of educational vouchers has played an important role in providing new hopes toward greater individual freedom, as well as empowerment, the concept of educational vouchers can also provide limited understanding and has dangerous implications in the field of education. The ambiguities and tensions of preschool vouchers in Hong Kong and Taiwan can provide a window to study the formation of governance and regulation that come together to sustain the production of new norms and standards in early childhood education and care (Lee, 2006;Yuen 2007). We should not ignore the effects of educational vouchers that could ironically perpetuate sociocultural differences by privileging certain families over others.…”
mentioning
confidence: 99%